Щодо змісту сучасної політики у сфері боротьби зі злочинністю, пов’язаної із забезпеченням особистої безпеки засуджених - Колб, І.; Пришко, І.; Kolb, I.; Pryshko, I. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
Протидія злочинності в місцях позбавлення волі, зокрема забезпечення права засуджених на особисту безпеку, і процес розвитку кримінально-правової політики вимагає внесення відповідних коректив у здійснен- ня оперативно-розшукової політики. Проаналізовано особливості, які характерні для сучасної оперативно- розшукової політики України в установах позбавлення волі та які пов’язані із забезпеченням права засуджених до позбавлення волі на особисту безпеку. In order to combat the crime in prisons, in particular to ensure prisoners’ rights to personal security, and to develop criminal justice policy it is obligatory to provide appropriate adjustments to the implementation of operational policies. Operatively-search policy in penitentiaries should be attributed to the subject of the study of the theory of operational activities. The main features that characterize modern operational policy of Ukraine in penitentiaries are associated with the provision of law sentenced to imprisonment for personal security. Among them the authors defines: a) the general regulation on the implementation of operational activities is open regulations; b) a distinct definition of entities of operational activities in penal institutions and their competencies; c) regulation law list search operations; d) public participation and individuals to assist operational units penal institutions; g) requirements for strict observance of legality in the activity of operational activities in penal institutions; e) limit the constitutional rights of prisoners in the course of operational activities only by law and in accordance with the established procedure
To the Content of Contemporary Policy of the Fight Against Crime Connected with the Providing the Prisoners’ Personal Security.
Keywords: кримінально-виконавче право; відбування покарання; боротьба зі злочинністю; crime prevention; to protect the personal safety of prisoners; penal law